Charter and Ordinances of the City of Macon (1853) Page 38, § 5 - (:unkn) unknown (General Publisher, 1853)
Prohibited the discharge of a gun, pistol, or any other fire-arms within three hundred yards of any house. Also prohibited burning rockets, crackers, or any kind of fireworks within the limits of the city. Violators fined not exceeding twenty dollars.
--
Keywords: DISCHARGE